Decoding ESG 4.0: Integrating Marketing Technology for Proactive Business Innovation Design Towards Sustainability in an Aging Society - สมบูรณ์, ธิติรัตน์; เอมชุ่มจิตต์, สุพจน์; เอกอริยะเจริญกุล, อชิรวีร์; เมฆบริบูรณ์, ตรีกาล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This academic article aims to: 1) develop an in-depth understanding of ESG 4.0 strategy components in the digital era; 2) analyze the role of Marketing Technology in enhancing sustainability within an aging society; and 3) design innovative business models and strategies for sustainable competitive advantage. The study employs Institutional Theory and the Resource-Based View as analytical frameworks within the context of Thailand’s transition into a Super-Aged Society and a Risk Society in 2026.          The findings reveal that integrating Marketing Technology with ESG 4.0 strategy is crucial for transitioning from reactive business operations to proactive innovation. This integration is synthesized into an innovative Business Model Canvas (BMC) that practically incorporates environmental, social, and governance dimensions with technology across four key pillars: 1) value propositions driven by hyper-personalization for well-being and trust as a product; 2) digital infrastructure enhancement through Marketing Technology ecosystems and Blockchain; 3) an engagement ecosystem focused on digital inclusion; and 4) financial balancing through Creating Shared Value (CSV). The conclusion highlights that leveraging technology for sustainability fosters organizational legitimacy and creates inimitable competitive advantages, which are decisive factors for resilient growth amidst long-term demographic crises.